NHS cancer services and systems—ten pressure points a UK cancer control plan needs to address - Aggarwal, Ajay; Simcock, Richard; Price, Pat; Rachet, Bernard; Lyratzopoulos, Georgios; Walker, Kate; Spencer, Katie; Roques, Tom; Sullivan, Richard (The lancet oncology, 2024)
In this Policy Review we discuss ten key pressure points in the NHS in the delivery of cancer care services that need to be urgently addressed by a comprehensive national cancer control plan. These pressure points cover areas such as increasing workforce capacity and its productivity, delivering effective cancer survivorship services, addressing variation in quality, fixing the reimbursement system for cancer care, and balancing of the cancer research agenda. These areas have been selected based on their relative importance to ensuring sustainable cancer services, persistence as key issues in the NHS, and their impact on delivering better and more equitable and affordable patient outcomes. Many of these pressure points are not acknowledged explicitly in any current discourse. The evidence we provide points to their impact on the ability to deliver world class cancer care, but also to their amenability to affordable solutions if given the relevant prioritisation and investment. The current narrative needs to move away from a technocentric approach to improving care, to one focused on understanding the complexity of cancer services and the wider health system to drive improvements in survival, quality of life, and experience for patients.